2011
DOI: 10.1537/asj.119.9
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Analysis on Human Skeletal Remains from the Edo-period Fushimi Castle Site in Japan

Abstract: The Edo period in Japan (AD 1603-1868) was characterized by the rapid increase and later stabilization of the population, as well as the development of both land and marine transport. Diet during the Edo-period can

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Sev eral statistical comparisons indicate a significant difference only between δ 13 C values of females and males during the Middle-Late period (Figure 4, Figure 5), although the dif ference is relatively small (0.37‰). Kusaka et al (2011) showed that δ 13 C values of adult males were significantly higher (+0.8‰) than those of adult females among Fushimi townspeople during the Edo period, similar to the sex differ ence observed in Ikenohata during the Middle-Late period. Although Tsutaya et al (2014) showed a significantly higher δ 15 N value for males (+0.7‰) than females in the Hitotsu bashi population of Edo city during the earlier Edo period, such a difference was not observed for the Ikenohata popu lation.…”
Section: Intra-population Differencessupporting
confidence: 73%
See 2 more Smart Citations
“…Sev eral statistical comparisons indicate a significant difference only between δ 13 C values of females and males during the Middle-Late period (Figure 4, Figure 5), although the dif ference is relatively small (0.37‰). Kusaka et al (2011) showed that δ 13 C values of adult males were significantly higher (+0.8‰) than those of adult females among Fushimi townspeople during the Edo period, similar to the sex differ ence observed in Ikenohata during the Middle-Late period. Although Tsutaya et al (2014) showed a significantly higher δ 15 N value for males (+0.7‰) than females in the Hitotsu bashi population of Edo city during the earlier Edo period, such a difference was not observed for the Ikenohata popu lation.…”
Section: Intra-population Differencessupporting
confidence: 73%
“…Kusaka et al (2011) also reported no significant isotopic difference among Fushimi townspeople from different subperiods. Historical studies have revealed some changes in food culture during the Edo period.…”
Section: Intra-population Differencesmentioning
confidence: 94%
See 1 more Smart Citation
“…The stable isotope ratios in bone collagen reflect those of the protein fraction of the diet (Tieszen and Fagre, 1993). By considering these factors, the palaeodiet, especially for dietary protein sources, can be reconstructed by measuring the stable isotope ratios of human skeletal collagen (e.g., Yoneda et al, 2004;Kusaka et al, 2011;Tsutaya et al, 2016a).…”
Section: Stable Isotope Analysismentioning
confidence: 99%
“…Although the diet of townspeople in the Edo period (AD 1603(AD -1867 in Japan has been reconstructed in detail, the diet of ordinary people living in villages has not been studied in similar depth. Historical (Hanley, 1997;Ehara et al, 2009;Harada, 2009), archaeological (Vaporis, 1998), and bioarchaeological (Kusaka et al, 2011;Tsutaya et al, 2016a;Maruyama et al, 2018) studies have revealed that the diet of ordinary people in the Edo period mainly comprised C 3 crops, such as rice and vegetables, and fishes and poultry were sometimes consumed. However, most of this evidence has come from larger cities, such as Edo (present-day Tokyo), Osaka, and Kyoto, and the everyday diet of people living in villages is not well documented.…”
Section: Introductionmentioning
confidence: 99%